Woordeboeke en Dowe gebruikers: huidige probleme en die behoefte aan beter oplossings - Fourie Blair, Hanelle (Lexikos, 2013)
Dictionaries and Deaf Users — Current Problems and the Need for Better Solutions. Sign language lexicography is a branch of lexicography that has until now been a largely vague, unimportant area. The development of sign language lexicography has in the past been subject to various forms of bias and limitation. Often it was not considered necessary to compile a bilingual dictionary in which it is also possible to look up a sign because bilingual sign language dictionaries were mostly aimed at hearing people who wanted to or had to learn the language. In addition to that it was very difficult, owing to the nature of printed dictionaries and the lack of a sign language orthography, to present and order signs so that they may be searched without using a written search term. Some notation systems were developed in an effort to circumvent this problem, but these systems never found widespread acceptance with regular users. The development of electronic sign language dictionaries however have caused a revolution in sign language lexicography. It is no longer unusual to find electronic sign language dictionaries in which it is not only possible to search for a word, but also for a sign, usually according to one or more of the sign's parameters, like handshape. Such dictionaries make it possible for a Deaf user to obtain direct access to his or her first language (sign language) without any knowledge of the second language (the written language). The article also points out a newly proposed model for very young Deaf users which allows them to also search for a sign or word via concept.